THE INFLUENCE OF HR QUALITY ON JOB SATISFACTION WITH JOB LOYALTY AS AN INTERVENING VARIABLE IN EMPLOYEES OF BPJS KETENAGAKERJAAN BRANCH MEDAN RAYA - Sarma Niasti Saragih; Kiki Farida Ferine (Lafadz Jaya Publisher, 2023)
This research aims to see how HR quality influences job satisfaction and influences job loyalty. This research was conducted at BPJS Employment Medan Raya Branch. The population used was 130 and the sample was made using the Slovin formula to 98 employees. The data source used is primary data and the data collection is questionnaires and surveys. The method used is associative and quantitative. The research model used is an analytical method. Research results: If HR Quality increases by 1%, Job Loyalty will increase by 1% and if HR Quality decreases, Job Loyalty will also decrease. If HR quality increases by 1%, Job Satisfaction will increase by 1% and vice versa, if HR quality decreases, Job Loyalty will decrease. If Job Loyalty increases by 1%, Job Satisfaction will increase by 1%. Conversely, if Job Loyalty decreases, Job Satisfaction will decrease. Indirectly, Job Loyalty influences HR Quality and Job Satisfaction in a positive and good way, as well as without loyalty, HR Quality can also influence Job Satisfaction positively.